Purple phosphor crystal powder, method for preparing the same and application thereof
Patent Information
- Application Number
- CN202611092472.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明旨在至少在一定程度上解决相关技术中的技术问题之一。为此,本发明提供了一种,紫磷晶体粉末及其制备方法与应用。本发明通过引入特定的碲、碘复合催化体系,显著缩短了反应时间、提高了紫磷产率,同时能够直接得到粉末形态的紫磷晶体,便于规模化应用。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional materials technology, specifically to purple phosphorus crystal powder, its preparation method, and its application. Background Technology
[0002] Compared to amorphous red phosphorus, crystalline phosphorus possesses a regular crystal structure, a fixed and measurable band gap, and semiconductor properties, and has garnered widespread attention and application in fields such as energy, optoelectronics, catalysis, biomedicine, and the environment. Among these, black phosphorus, benefiting from its unique two-dimensional structure and excellent physicochemical properties, exhibits outstanding performance advantages in these fields and is considered a highly promising two-dimensional semiconductor material. Purple phosphorus, with its layered structure highly similar to black phosphorus, should theoretically also possess broad application prospects, especially in the field of high-performance two-dimensional semiconductor materials and devices. Furthermore, purple phosphorus has a higher band gap than bulk black phosphorus, giving it a unique advantage in the field of wide-bandgap semiconductors (such as laser modulation and infrared photodetectors).
[0003] However, most methods for synthesizing purple phosphorus rely on high-temperature chemical vapor transport. While alternative methods such as flux-assisted synthesis and phase-selective synthesis via solid-state thermal conversion have emerged in recent years, all these methods require long reaction times, sometimes several days or even a week, and have low yields, severely hindering the large-scale preparation and widespread application of purple phosphorus materials. Furthermore, traditional chemical vapor transport methods primarily yield bulk purple phosphorus single crystals, while practical applications (such as biomedicine, flame retardancy, energy storage, and catalysis) require micro- and nano-scale purple phosphorus powders. Directly using bulk single crystals not only necessitates additional high-energy pulverization processes but also easily introduces impurities and defects, increasing production energy consumption and application costs.
[0004] Therefore, there is an urgent need for a synthesis method that can directly and rapidly convert amorphous red phosphorus powder into purple phosphorus crystal powder, in order to overcome the defects of related technologies such as excessively long reaction time, low yield, and mismatch between product morphology and application requirements. Summary of the Invention
[0005] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, this invention provides a purple phosphorus crystalline powder, its preparation method, and its applications. By introducing a specific tellurium-iodine composite catalytic system, this invention significantly shortens the reaction time, increases the yield of purple phosphorus, and directly obtains purple phosphorus crystals in powder form, facilitating large-scale application.
[0006] A first aspect of the present invention provides a method for preparing purple phosphorus crystal powder, comprising: A mixture of amorphous red phosphorus, tellurium, and iodine is placed in a reactor; The reactor was subjected to vacuuming and sealing. The sealed reactor is then subjected to heat treatment to obtain the purple phosphorus crystal powder.
[0007] Therefore, by introducing a tellurium and iodine composite catalytic system, the synergistic effect of tellurium and iodine significantly shortens the synthesis time of purple phosphorus crystal powder, greatly reduces production energy consumption and time costs, and improves yield. This invention can directly obtain purple phosphorus crystals in powder form, avoiding the additional high-energy crushing process required in related technologies because the product is a bulk single crystal, thereby reducing the introduction of impurities and lattice defects, and improving product purity and crystal quality. The preparation process of this invention is simple and the raw materials are readily available. The obtained purple phosphorus crystal powder has a fine particle size and good dispersibility. Purple phosphorus nanosheets can be obtained by liquid phase exfoliation without complex pretreatment. It is suitable for various application scenarios such as optoelectronic devices, catalysis, and flame retardancy, and has high value for large-scale application.
[0008] According to an embodiment of the present invention, the above preparation method may further include at least one of the following additional technical features: In some embodiments, the heat treatment includes three stages: heating, holding, and cooling; preferably, the heat treatment satisfies at least one of the following conditions: The heat treatment is performed at a holding temperature of 400 ℃ to 575 ℃ for a holding time of 0 h to 6 h. The heating rate of the heat treatment is 5 ℃ / min to 10 ℃ / min; The cooling rate of the heat treatment is 0.2 ℃ / min to 3 ℃ / min.
[0009] This will help to further shorten the synthesis time of purple phosphorus crystal powder and improve the purity, crystallinity and yield of the product.
[0010] In some embodiments, the mass ratio of amorphous red phosphorus, tellurium, and iodine is (5~40):(0.5~5):1. This is beneficial for improving catalytic efficiency while reducing raw material waste.
[0011] In some embodiments, the vacuum level of the reactor after sealing is 1×10⁻⁴ Pa to 10 Pa. This reduces the gas phase transport rate and increases the yield.
[0012] In some embodiments, the preparation method satisfies at least one of the following conditions: The heating temperature at one end of the reactor is 400℃~560℃, and the heating temperature at the opposite end is 415℃~575℃. After the heat treatment, the preparation method further includes washing and vacuum drying the purple phosphorus crystal powder.
[0013] This helps to remove impurities from the purple phosphorus crystal powder and improve its purity.
[0014] A second aspect of the present invention provides a purple phosphorus crystal powder, prepared by the aforementioned method. Therefore, the purple phosphorus crystal powder has high purity and excellent crystallinity, and can be used directly without pulverization. The purple phosphorus crystal powder has better thermal stability than black phosphorus and good exfoliation properties, making it easy to obtain few-layer purple phosphorus nanosheets through liquid-phase exfoliation, facilitating its application. Furthermore, the purple phosphorus crystal powder possesses all the features and advantages of the aforementioned preparation method, which will not be repeated here.
[0015] In some embodiments, the purple phosphorus crystal powder has a sheet-like structure; Preferably, the maximum lateral dimension of the sheet-like structure is 1 μm to 30 μm; Preferably, the thickness of the sheet-like structure is 0.1 μm to 5 μm.
[0016] Therefore, the purple phosphorus crystal powder is small in size and does not need to undergo the high-energy crushing process of bulk crystals, which helps to reduce energy consumption and production costs.
[0017] A third aspect of the present invention provides a purple phosphorus two-dimensional nanosheet, which is obtained by liquid-phase exfoliation from purple phosphorus crystal powder prepared by the aforementioned preparation method. Therefore, the purple phosphorus two-dimensional nanosheet possesses the excellent photoelectric properties of a two-dimensional semiconductor. Furthermore, the purple phosphorus two-dimensional nanosheet possesses all the features and advantages of the aforementioned preparation method or purple phosphorus crystal powder, which will not be repeated here.
[0018] In some embodiments, the purple phosphorus two-dimensional nanosheets satisfy at least one of the following conditions: The purple phosphorus two-dimensional nanosheets have a rectangular structure; The maximum lateral dimension of the purple phosphorus two-dimensional nanosheets is 0.5 μm to 3 μm; The thickness of the purple phosphorus two-dimensional nanosheets is 1 nm to 100 nm.
[0019] A fourth aspect of the present invention provides an application of the purple phosphorus crystal powder, or the aforementioned purple phosphorus crystal powder, or the aforementioned purple phosphorus two-dimensional nanosheets, prepared by the aforementioned preparation method, in the fields of optoelectronics, catalysis, energy storage, flame retardancy, or biomedicine. Thus, the application possesses all the features and advantages of the aforementioned preparation method, or purple phosphorus crystal powder, or purple phosphorus two-dimensional nanosheets, which will not be elaborated further here.
[0020] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0021] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 A photograph of the purple phosphorus crystal powder prepared in Example 1 of this invention; Figure 2 This is a SEM image of the purple phosphorus crystal powder prepared in Example 1 of the present invention; Figure 3 The XRD pattern of the purple phosphorus crystal powder prepared in Example 1 of this invention; Figure 4 The Raman spectrum of the purple phosphorus crystal powder prepared in Example 1 of this invention; Figure 5 This is a TEM image of the two-dimensional phosphorus nanosheets obtained by liquid phase exfoliation of the phosphorus crystal powder described in Example 1. Figure 6 The image shows an HRTEM image of two-dimensional phosphorus nanosheets obtained by liquid phase exfoliation of the phosphorus crystal powder described in Example 1. Detailed Implementation
[0022] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0023] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. Furthermore, in the description of this invention, unless otherwise stated, "a plurality of" means two or more.
[0024] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0025] In this document, the terms “comprising” or “including” are open-ended expressions, meaning that they include the contents specified in this invention, but do not exclude other aspects.
[0026] In this document, the terms “optionally,” “optionally,” or “optionally” generally refer to an event or condition that may, but may not, occur, and the description includes both cases in which the event or condition occurs and cases in which the event or condition does not occur.
[0027] A first aspect of the present invention provides a method for preparing purple phosphorus crystal powder, comprising: A mixture of amorphous red phosphorus, tellurium, and iodine is placed in a reactor; The reactor was subjected to vacuuming and sealing. The sealed reactor is then subjected to heat treatment to obtain the purple phosphorus crystal powder.
[0028] Therefore, using amorphous red phosphorus as a raw material is low-cost and widely available. By introducing a tellurium and iodine composite catalytic system, the two work synergistically, significantly reducing the amount of catalyst used and lowering costs. Furthermore, tellurium is soluble in acidic hydrogen peroxide solution, and iodine has a low sublimation temperature, is easily volatile, and is soluble in ethanol; therefore, both can be easily removed during post-processing, which is beneficial for improving product purity. Tellurium and iodine catalyze a solid-phase transformation of amorphous red phosphorus at high temperatures, converting it from an amorphous phase to crystalline purple phosphorus powder, significantly shortening the synthesis time of purple phosphorus crystalline powder (this invention can control the total synthesis time, including heating time, holding time, and cooling time, to within 7.8 hours). Within h), the total energy consumption of heat treatment is reduced, and the yield is improved. This invention can directly obtain purple phosphorus crystals in powder form, avoiding the additional high-energy crushing process required in related technologies because the product is a bulk single crystal. This reduces the introduction of impurities and lattice defects, and improves the purity and crystal quality of the product. The preparation process of this invention is simple and the raw materials are readily available. The obtained purple phosphorus crystal powder has a small particle size and good dispersibility. Purple phosphorus nanosheets can be obtained by liquid phase exfoliation without complex pretreatment. It is suitable for various application scenarios such as optoelectronic devices, catalysis, and flame retardancy, and has high value for large-scale application.
[0029] In some embodiments, the mass ratio of amorphous red phosphorus, tellurium, and iodine is (5~40):(0.5~5):1. This helps to reduce raw material waste while improving catalytic efficiency. Specifically, the ratio can be 5:0.5:1, 10:1:1, 10:2:1, 20:0.5:1, 20:5:1, 40:1:1, 40:5:1, etc. This helps to fully utilize the synergistic catalytic effect of tellurium and iodine, improve catalytic efficiency, promote the rapid conversion of amorphous red phosphorus to the purple phosphorus crystalline phase, and improve the yield and purity of purple phosphorus crystalline powder. If the amount of red phosphorus is too high, it may significantly reduce the phase change reaction rate and prolong the reaction time; if the amount of red phosphorus is too low, it may increase impurity residues, make purification difficult, and reduce product purity.
[0030] In some embodiments, the reactor comprises a tubular reactor, such as a quartz tube; specifically, amorphous red phosphorus, tellurium, and iodine may be placed at one end of the tubular reactor.
[0031] In some embodiments, the vacuum degree of the reactor after sealing is 1×10⁻⁴ Pa to 10 Pa, specifically 1×10⁻⁴ Pa, 1×10⁻³ Pa, 1×10⁻² Pa, 0.1 Pa, 1 Pa, 5 Pa, 10 Pa, etc. This facilitates the control of the transport rate of gaseous species within the reactor, allowing gaseous iodine and tellurium to be fully adsorbed on the surface of red phosphorus and participate in the catalytic reaction, thereby improving the yield and crystal uniformity of purple phosphorus crystal powder. If the vacuum is too high, residual gases (such as oxygen, water vapor, etc.) may inhibit the catalytic activity of tellurium and iodine, leading to the oxidation of red phosphorus and reducing the purity of the purple phosphorus product; if the vacuum is too low, the transport of gaseous species is too sparse, which may result in insufficient supply of active species on the surface of red phosphorus, slowing down the crystal growth rate of purple phosphorus and making it difficult to obtain a highly crystalline product in a short time.
[0032] It should be noted that the "vacuum degree" mentioned in this invention refers to absolute vacuum (i.e., absolute pressure), not relative vacuum (gauge pressure). As is known to those skilled in the art, absolute vacuum is a pressure value measured with zero pressure as the reference, while relative vacuum is a negative pressure value measured with atmospheric pressure as the reference; the two differ in value by approximately one standard atmosphere. In this invention, unless otherwise specified, all vacuum degrees refer to the absolute pressure inside the reactor. A higher vacuum degree value indicates a higher absolute pressure inside the reactor, i.e., a lower vacuum level; conversely, a lower vacuum degree value indicates a lower absolute pressure inside the reactor, i.e., a higher vacuum level.
[0033] In some embodiments, the sealing process includes flame sealing.
[0034] In some embodiments, specifically, the vacuum treatment and sealing treatment includes: pumping the quartz tube to a specified pressure value using a mechanical pump and a molecular pump, then heating the sealing area of the quartz tube using an oxyhydrogen flame vacuum sealing machine, rotating the quartz tube to ensure uniform heating, and after a period of time, the area softens and concaves inward to form a neck; adding a quartz column to hold the neck in place, continuing to heat the quartz column, and melting and sealing to form a sealed space.
[0035] In some embodiments, the heat treatment includes three stages: heating, holding, and cooling.
[0036] In some embodiments, the heat treatment holding temperature is 400 ℃~575 ℃, and the holding time is 0 h~6 h; for example, the heat treatment holding temperature can be 400 ℃, 420 ℃, 450 ℃, 480 ℃, 500 ℃, 520 ℃, 560 ℃, 575 ℃, etc.; the holding time can be 0 h, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 6 h, etc. This is beneficial for further shortening the synthesis time of purple phosphorus crystal powder, promoting the phase transformation of amorphous red phosphorus to purple phosphorus crystals, and improving the conversion rate, product purity, crystallinity, and yield of purple phosphorus crystal powder. If the holding temperature is too low, it may be difficult to effectively drive the phase transformation of red phosphorus to purple phosphorus, resulting in a large amount of residual amorphous phase in the product; if the holding temperature is too high, side reactions such as decomposition or transformation into other allotropes may occur, reducing the purity of purple phosphorus. If the holding time is too short, the crystal phase transformation may be incomplete and the yield may be low; if the holding time is too long, the production cycle may be prolonged and energy consumption may be increased, which is not conducive to industrialization.
[0037] In some embodiments, the heating rate of the heat treatment (i.e., the rate at which the temperature rises from room temperature to the heat treatment temperature) is 5°C / min to 10°C / min; for example, it can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc. This facilitates the rapid transition of the reaction system across the phase transition temperature range from amorphous red phosphorus to purple phosphorus, shortens the time consumed in the heating stage, and forms uniform crystal nuclei during the heating process, thereby improving the crystallinity of the purple phosphorus powder. If the heating rate is too slow, the reaction system may remain in the amorphous region for too long, potentially causing structural relaxation of red phosphorus in the low-temperature region, which may reduce the conversion rate. If the heating rate is too fast, uneven heat transfer may occur, easily leading to localized poor crystallization or uneven grain size, thus reducing the crystal quality of the product.
[0038] In some embodiments, the cooling rate of the heat treatment is 0.2 ℃ / min to 3 ℃ / min; for example, it can be 0.2 ℃ / min, 0.5 ℃ / min, 1 ℃ / min, 1.5 ℃ / min, 2 ℃ / min, 2.5 ℃ / min, 3 ℃ / min, etc. This is beneficial for improving the crystallinity of the purple phosphorus crystal powder and reducing lattice defects. If the cooling rate is too slow, it is easy to prolong the synthesis cycle and increase energy consumption and production costs; if the cooling rate is too fast, large thermal stress may be generated inside the crystal, which can easily lead to lattice distortion or microcracks, reducing the crystal quality of the product.
[0039] In some embodiments, the heating temperature at one end of the reactor is 400℃~560℃, and the heating temperature at the opposite end is 415℃~575℃; for example, the heating temperature at one end of the reactor can be 400℃, 420℃, 450℃, 480℃, 500℃, 520℃, 560℃, etc., and the heating temperature at the opposite end can be 415℃, 435℃, 465℃, 495℃, 515℃, 535℃, or 575℃, etc. Specifically, when amorphous red phosphorus, tellurium, and iodine are placed at one end of the reactor heated to 400℃~560℃, purple phosphorus crystal powder is also generated at that end. Therefore, by setting different heating temperatures at both ends of the reactor, a certain temperature gradient is created inside the reactor. This facilitates the directional transport of gaseous iodine and tellurium from the high-temperature end to the low-temperature end, allowing them to accumulate on the surface of red phosphorus at the low-temperature end and participate in the catalytic reaction. Simultaneously, it promotes the preferential nucleation and growth of purple phosphorus crystals at the low-temperature end, thus increasing the yield of purple phosphorus crystal powder. If the temperature difference between the two ends is too small, the directional transport of gaseous species will be insufficient, potentially leading to poor catalyst distribution uniformity and hindering the efficient formation of purple phosphorus. If the temperature difference is too large, the low-temperature end may be too cold, making the phase change reaction difficult to carry out effectively, while the high-temperature end may be too hot, potentially causing product decomposition or the formation of other phosphorus allotropes, reducing the yield and purity of purple phosphorus crystal powder.
[0040] In some embodiments, the heat treatment equipment includes a dual-zone tubular furnace; specifically, the dual-zone tubular furnace has a low-temperature end and a high-temperature end, the low-temperature end temperature is 400 ℃~560 ℃ (e.g. 400 ℃, 420 ℃, 450 ℃, 480 ℃, 500 ℃, 520 ℃, 560 ℃, etc.), and the high-temperature end temperature is 415 ℃~575 ℃ (e.g. 415 ℃, 435 ℃, 465 ℃, 495 ℃, 515 ℃, 535 ℃, 575 ℃, etc.).
[0041] In some embodiments, after the heat treatment, the preparation method further includes washing and vacuum drying the purple phosphorus crystal powder. This helps to remove impurities from the purple phosphorus crystal powder and improve its purity.
[0042] In some embodiments, the detergent used for washing includes at least one of hydrogen peroxide solution and ethanol.
[0043] A second aspect of the present invention provides a purple phosphorus crystal powder, prepared by the aforementioned method. Therefore, the purple phosphorus crystal powder has high purity and excellent crystallinity, and can be used directly without pulverization. The purple phosphorus crystal powder has better thermal stability than black phosphorus and good exfoliation properties, making it easy to obtain few-layer purple phosphorus nanosheets through liquid-phase exfoliation, facilitating its application. Furthermore, the purple phosphorus crystal powder possesses all the features and advantages of the aforementioned preparation method, which will not be repeated here.
[0044] In some embodiments, the purple phosphorus crystal powder has a sheet-like structure; Preferably, the maximum lateral dimension of the sheet-like structure is 1 μm to 30 μm; for example, it can be 1 μm, 2 μm, 5 μm, 10 μm, 20 μm, 30 μm, etc. Therefore, the purple phosphorus crystal powder has a small size, allowing for direct liquid-phase exfoliation or dispersion processing in subsequent applications without undergoing the high-energy crushing process of bulk crystals, thus helping to maintain the crystal integrity of the product while ensuring uniform dispersion. If the maximum lateral dimension is too large, the specific surface area of the purple phosphorus crystal powder may be too small, reducing its surface activity and making it difficult to obtain nanosheets of uniform thickness during liquid-phase exfoliation; if the maximum lateral dimension is too small, it may lead to an increase in edge defects in the purple phosphorus crystals, a decrease in crystallinity, and a weakening of semiconductor performance.
[0045] Preferably, the thickness of the sheet-like structure is 0.1 μm to 5 μm; specifically, it can be 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc. This is beneficial for improving the crystallinity of the purple phosphorus crystal powder, facilitating the subsequent acquisition of few-layer or single-layer nanosheets through liquid-phase exfoliation, and providing sufficient active sites for applications such as catalysis and energy storage. If the thickness of the sheet-like structure is too thin, it may reduce the structural stability of the crystal and make it prone to breakage during preparation or processing; if the thickness of the sheet-like structure is too thick, it may weaken its anisotropic properties and reduce semiconductor performance.
[0046] A third aspect of the present invention provides a purple phosphorus two-dimensional nanosheet, which is obtained by liquid-phase exfoliation from purple phosphorus crystal powder prepared by the aforementioned preparation method. Therefore, the purple phosphorus two-dimensional nanosheet possesses the excellent photoelectric properties of a two-dimensional semiconductor. Furthermore, the purple phosphorus two-dimensional nanosheet possesses all the features and advantages of the aforementioned preparation method or purple phosphorus crystal powder, which will not be repeated here.
[0047] In some embodiments, the purple phosphorus two-dimensional nanosheets have a rectangular structure.
[0048] In some embodiments, the maximum lateral dimension of the purple phosphorus two-dimensional nanosheets is 0.5 μm to 3 μm; for example, it can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 3 μm, etc. This is beneficial for achieving uniform dispersion and device fabrication in optoelectronic devices, catalysis, and biomedicine. If the maximum lateral dimension of the nanosheets is too large, it is not conducive to forming a stable dispersion system and may reduce the consistency of device performance; if the maximum lateral dimension of the nanosheets is too small, the proportion of crystal edges increases and defects increase, which may lead to a decrease in carrier mobility and reduce semiconductor performance.
[0049] In some embodiments, the thickness of the purple phosphorus two-dimensional nanosheets is 1 nm to 100 nm; specifically, it can be 1 nm, 5 nm, 10 nm, 25 nm, 50 nm, 75 nm, 100 nm, etc. This is beneficial for improving the specific surface area, carrier mobility, and two-dimensional semiconductor properties of the purple phosphorus two-dimensional nanosheets while maintaining the two-dimensional sheet structure. If the thickness of the purple phosphorus nanosheets is too thin, it may reduce the mechanical strength and chemical stability of the sheet structure, making it prone to breakage or oxidation during processing or device fabrication; if the thickness of the purple phosphorus nanosheets is too thick, it may weaken its two-dimensional quantum confinement effect, leading to a reduced band gap, decreased carrier mobility, and reduced semiconductor performance.
[0050] In some embodiments, the liquid phase exfoliation process includes: mixing purple phosphorus crystal powder with a solvent, sonicating, and centrifuging to obtain purple phosphorus two-dimensional nanosheets.
[0051] A fourth aspect of the present invention provides an application of the purple phosphorus crystal powder, or the aforementioned purple phosphorus crystal powder, or the aforementioned purple phosphorus two-dimensional nanosheets, prepared by the aforementioned method, in the fields of optoelectronics, catalysis, energy storage, flame retardancy, or biomedicine. Optionally, the purple phosphorus nanosheets can be applied in photodetectors, field-effect transistors, photovoltaic cells, or light-emitting diodes; or used as photocatalysts or electrocatalysts in the fields of water splitting to produce hydrogen, oxygen reduction, or carbon dioxide reduction; or used as negative electrode active materials in lithium-ion batteries or sodium-ion batteries; or dispersed in a polymer matrix as a flame-retardant additive; or used as a photothermal therapy agent or drug delivery carrier. Thus, the applications possess all the features and advantages of the aforementioned preparation methods, or purple phosphorus crystal powder, or purple phosphorus two-dimensional nanosheets, which will not be elaborated further here.
[0052] It should be noted that, in this invention, the maximum lateral dimension refers to the maximum distance between any two points on the outline of the sheet-like structure or the purple phosphorus two-dimensional nanosheet, that is, the maximum span in the in-plane direction of the sheet-like structure or the purple phosphorus two-dimensional nanosheet. It should be understood that regardless of whether it is approximately circular, elliptical, polygonal, or irregular in shape, its in-plane dimension can be accurately characterized by this definition. The maximum lateral dimension is obtained by measuring scanning electron microscopy (SEM) or transmission electron microscopy (TEM) images; specifically, at least 50 purple phosphorus crystal powder sheet-like structures or purple phosphorus two-dimensional nanosheets are randomly selected under SEM or TEM for measurement, and the maximum lateral dimension is obtained by averaging the multiple measurement results based on the maximum distance between any two points on the outline of each nanosheet.
[0053] The present invention will be explained below with reference to embodiments. Those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of the invention. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0054] Example 1 (1) Weigh 400 mg of commercial amorphous red phosphorus powder, 20 mg of commercial tellurium powder and 10 mg of block iodine according to the mass ratio of amorphous red phosphorus, tellurium and iodine of 40:2:1. Mix them evenly and put them into a quartz tube sealed at one end (the quartz tube has a length of 140 mm, an outer diameter of 10 mm and an inner diameter of 8 mm). (2) Use an oxyhydrogen flame vacuum sealing machine to evacuate the quartz tube to a vacuum and then flame seal it, with the vacuum level controlled at 1×10-4 Pa; (3) The flame-sealed quartz tube was placed horizontally in a dual-temperature zone tube furnace and heated to the set temperature at a rate of 5 °C / min. The set temperature at the low temperature end was 500 °C and the set temperature at the high temperature end was 515 °C. After reacting at this temperature for 3 h, it was cooled to room temperature at a rate of 1.25 °C / min. (4) Take out the quartz tube, break it and collect the product from the raw material end. Wash it with acidic hydrogen peroxide solution and ethanol in sequence to remove the catalyst tellurium and iodine. After vacuum drying, the purified purple phosphorus crystal powder is obtained.
[0055] Example 2 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that: The mass ratio of the amorphous red phosphorus, tellurium, and iodine is 40:5:1; The vacuum level is controlled at 1×10⁻³ Pa; The temperature was increased to the set temperature at a rate of 6 °C / min, with the set temperature at the low-temperature end being 480 °C and the set temperature at the high-temperature end being 495 °C. After holding the reaction at this temperature for 0 h, the temperature was cooled to room temperature at a rate of 1.5 °C / min.
[0056] Example 3 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that: The mass ratio of amorphous red phosphorus, tellurium, and iodine is 20:1:1; The vacuum level is controlled at 1×10⁻² Pa; The temperature was increased to the set temperature at a rate of 7 °C / min, with the set temperature at the low-temperature end being 450 °C and the set temperature at the high-temperature end being 465 °C. After holding the reaction at this temperature for 4 hours, the temperature was cooled to room temperature at a rate of 2 °C / min.
[0057] Example 4 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that: The mass ratio of amorphous red phosphorus, tellurium, and iodine is 10:0.5:1; The vacuum level is controlled at 0.1 Pa; The temperature was increased to the set temperature at a rate of 8 °C / min, with the set temperature at the low-temperature end being 420 °C and the set temperature at the high-temperature end being 435 °C. After holding the reaction at this temperature for 5 h, the temperature was cooled to room temperature at a rate of 3 °C / min.
[0058] Example 5 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that: The mass ratio of amorphous red phosphorus, tellurium, and iodine is 5:0.5:1; The vacuum level is controlled at 10 Pa; The temperature was increased to the set temperature at a rate of 10 °C / min, with the set temperature at the low-temperature end being 400 °C and the set temperature at the high-temperature end being 415 °C. After holding the reaction at this temperature for 6 h, the temperature was cooled to room temperature at a rate of 0.5 °C / min.
[0059] Example 6 This embodiment is based on Embodiment 1, and the only difference from Embodiment 1 is that: The set temperature for the low-temperature end was 560 ℃, and the set temperature for the high-temperature end was 575 ℃. After holding the reaction at this temperature for 3 hours, it was cooled to room temperature at a cooling rate of 0.2 ℃ / min.
[0060] Comparative Example 1 This comparative example is based on Example 1, and the only difference from Example 1 is that: this comparative example uses an equal amount of iodine instead of tellurium in Example 1, that is, this comparative example uses 400 mg of amorphous red phosphorus powder and 30 mg of block iodine, without tellurium, and the mass ratio of amorphous red phosphorus to iodine is 40:3.
[0061] Comparative Example 2 This comparative example is based on Example 1, and the only difference from Example 1 is that an equal amount of tellurium is used in this comparative example instead of iodine in Example 1. That is, this comparative example uses 400 mg of amorphous red phosphorus powder and 30 mg of commercial tellurium powder, without using iodine, and the mass ratio of amorphous red phosphorus to tellurium is 40:3.
[0062] Performance testing 1. The purple phosphorus crystal powder prepared in Example 1 was photographed and subjected to tests such as scanning electron microscopy (SEM), X-ray diffraction (XRD), and Raman spectroscopy. Figures 1-4 As shown.
[0063] 2. The purple phosphorus crystal powder obtained in Example 1 was subjected to liquid-phase exfoliation. Specifically, 5 mg of purple phosphorus crystal powder was added to 5 mL of isopropanol solution, and the mixture was ultrasonically treated at 40 kHz for 30 min. After centrifugation, a product between 2 k rpm and 8 k rpm was obtained, yielding purple phosphorus two-dimensional nanosheets. The purple phosphorus two-dimensional nanosheets were tested using transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM), as shown below. Figures 5-6 As shown.
[0064] 3. The yield of the purple phosphorus crystal powder prepared in Examples 1-6 and Comparative Examples 1-2 was calculated using the weighing method. First, the X-ray diffraction (XRD) spectrum of the product was used to determine whether it was purple phosphorus. If the XRD pattern did not match the standard spectrum of purple phosphorus, it proved that other crystal forms of elemental phosphorus had been obtained, and the yield was 0. Figure 1 If there are no other peaks, the product is considered to be pure purple phosphorus. The yield can be calculated using the following formula based on the mass of the purple phosphorus crystal powder and the mass of the amorphous red phosphorus added as raw material. The results are recorded in Table 1.
[0065] The formula for calculating the yield is:
[0066] Table 1. Yields of purple phosphorus crystal powders prepared in Examples 1-6 and Comparative Examples 1-2
[0067] Based on the test results, Figure 2 The two-dimensional plate-like structure of purple phosphorus can be observed; Figure 3 The diffraction peaks of the purple phosphorus crystal powder described herein match those of the purple phosphorus standard card, exhibiting sharp characteristic peaks. Figure 4 The characteristic peaks of purple phosphorus can also be clearly observed, confirming that the purple phosphorus crystal powder has high phase purity and crystallinity.
[0068] Figure 5 The morphology and size of the purple phosphorus two-dimensional nanosheets could be observed, indicating that they were successfully prepared. Figure 6 The large-scale uniform lattice fringes demonstrate that the purple phosphorus two-dimensional nanosheets have extremely high crystallinity.
[0069] The yields of Examples 1-6 were significantly higher than those of Comparative Examples 1-2, indicating that the present invention uses a tellurium-iodine composite catalyst, which significantly improves catalytic efficiency, shortens reaction time, and increases yield.
[0070] In the description of this specification, the references to terms such as "an embodiment," "some embodiments," "a method of implementation," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0071] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A method for preparing purple phosphorus crystal powder, characterized in that, include: A mixture of amorphous red phosphorus, tellurium, and iodine is placed in a reactor; The reactor was subjected to vacuuming and sealing. The sealed reactor is then subjected to heat treatment to obtain the purple phosphorus crystal powder.
2. The preparation method according to claim 1, characterized in that, The heat treatment includes three stages: heating, holding, and cooling; preferably, the heat treatment satisfies at least one of the following conditions: The heat treatment is performed at a holding temperature of 400 ℃ to 575 ℃ for a holding time of 0 h to 6 h. The heating rate of the heat treatment is 5 ℃ / min to 10 ℃ / min; The cooling rate of the heat treatment is 0.2 ℃ / min to 3 ℃ / min.
3. The preparation method according to claim 1 or 2, characterized in that, The mass ratio of amorphous red phosphorus, tellurium and iodine is (5~40):(0.5~5):
1.
4. The preparation method according to claim 1 or 2, characterized in that, The vacuum degree of the reactor after sealing is 1×10⁻⁴ Pa to 10 Pa.
5. The preparation method according to claim 1 or 2, characterized in that, At least one of the following conditions must be met: The heating temperature at one end of the reactor is 400℃~560℃, and the heating temperature at the opposite end is 415℃~575℃. After the heat treatment, the preparation method further includes washing and vacuum drying the purple phosphorus crystal powder.
6. A purple phosphorus crystal powder, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 5.
7. The purple phosphorus crystal powder according to claim 6, characterized in that, The purple phosphorus crystal powder has a plate-like structure; Preferably, the maximum lateral dimension of the sheet-like structure is 1 μm to 30 μm; Preferably, the thickness of the sheet-like structure is 0.1 μm to 5 μm.
8. A purple phosphorus two-dimensional nanosheet, characterized in that, The purple phosphorus crystal powder prepared by any one of claims 1 to 5 or the purple phosphorus crystal powder of claim 6 or 7 is obtained by liquid phase exfoliation process.
9. The purple phosphorus two-dimensional nanosheets according to claim 8, characterized in that, At least one of the following conditions must be met: The purple phosphorus two-dimensional nanosheets have a rectangular structure; The maximum lateral dimension of the purple phosphorus two-dimensional nanosheets is 0.5 μm ~ 3 μm; The thickness of the purple phosphorus two-dimensional nanosheets is 1 nm to 100 nm.
10. The application of a purple phosphorus crystal powder prepared by any one of claims 1 to 5, or the purple phosphorus crystal powder of claim 6 or 7, or the purple phosphorus two-dimensional nanosheets of claim 8 or 9, in the fields of optoelectronics, catalysis, energy storage, flame retardancy, or biomedicine.